2017
DOI: 10.12971/agrotec.v8i1.5302
|View full text |Cite
|
Sign up to set email alerts
|

Influência Da Adubação Fosfatada E Coberturas Vegetais Na Qualidade De Sementes De Feijão

Abstract: Resumo: Para auxiliar empresas produtoras de sementes na Objetivou-se com este trabalho, avaliar os efeitos das palhadas formadas por diferentes cultivos sobre a qualidade fisiológica de sementes de feijoeiro submetida a doses crescentes de P em semeadura. A pesquisa foi conduzida no período de inverno de 2010 e 2011, no Município de Selvíria, MS. O delineamento experimental foi o de blocos casualizados, em esquema de parcelas subdivididas com quatro repetições. As parcelas foram constituídas por: milheto, cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The importance of cover crops in protecting the soil surface and therefore increasing plant-available water is well-known (Nielsen et al, 2015) and may have a key role in seed production. Abrantes et al (2015) and Silva et al (2017) reported that common bean plants under straw-covered soils produced seeds with higher final germination percentage (92-98%) compared to bare soils (76-88%). Furthermore, the use of cover crops may lead to an increase of nutrient availability to the parent plant during the period of seed filling, resulting in high quality seeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of cover crops in protecting the soil surface and therefore increasing plant-available water is well-known (Nielsen et al, 2015) and may have a key role in seed production. Abrantes et al (2015) and Silva et al (2017) reported that common bean plants under straw-covered soils produced seeds with higher final germination percentage (92-98%) compared to bare soils (76-88%). Furthermore, the use of cover crops may lead to an increase of nutrient availability to the parent plant during the period of seed filling, resulting in high quality seeds.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the influence of cover crops, primarily grass-legume mixtures, on the physiological quality of common bean seeds. To the best of our knowledge, only two studies have assessed the influence of cover crops on common bean seed quality (Abrantes et al, 2015;Silva et al, 2017). In addition, topdressing N fertilization is a widespread practice to sustain high yields of common bean.…”
Section: Introductionmentioning
confidence: 99%